Komparasi Stabilitas dan Efektifitas Phyton dengan C++ Sebagai Algoritma Pemrograman Pemecahan Masalah pada Programmer Pemula - Elsa Nandita; Yahfizham Yahfizham (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Increasingly, more and more changes and advances are occurring, especially in the technology sector which requires users to understand and understand the meaning of an algorithm command. Basically, algorithms are steps used to solve problems. In the world of computing, programming algorithms are packaged by collaborating machine language with human desires. This article aims to compare the stability and effectiveness of machine languages that are often used by programmers. This article uses a systematic literature review method with sources from several studies and papers that have been conducted. The results of this study show that there are advantages and disadvantages of python and C++ respectively.